2021
DOI: 10.1016/j.ijmedinf.2021.104571
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effective factors of using mHealth apps for monitoring COVID-19 symptoms and contact tracing: A survey among Iranian citizens

Abstract: Background and objectives The use of mHealth applications depends on cognitive and social factors of individuals in different nations. This study aimed to identify the factors influencing the use of mHealth applications for both “ contact-tracing ” and “ symptom-monitoring” of COVID-19 among Iranian citizens. Methods A cross-sectional study with an online survey was conducted among Iranian citizens. Correlation calculation and multiple linear regression analysis were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 55 publications
2
8
0
1
Order By: Relevance
“…Moreover, there were a few other unexpected results. The clusters were predictive of the intention to use and the adoption of the CM app in wave 2, which is in line with papers that have put forward these psychosocial perceptions as being explanatory of the adoption of CTAs [ 5 , 13 - 16 ]. However, when the intention to use and the adoption of the CM app from wave 1 were added to the model, the clusters had less predictive power.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, there were a few other unexpected results. The clusters were predictive of the intention to use and the adoption of the CM app in wave 2, which is in line with papers that have put forward these psychosocial perceptions as being explanatory of the adoption of CTAs [ 5 , 13 - 16 ]. However, when the intention to use and the adoption of the CM app from wave 1 were added to the model, the clusters had less predictive power.…”
Section: Discussionsupporting
confidence: 88%
“…Previous research during the COVID-19 crisis has already shown that there are several determinants for the adoption of CTAs [1,5,[9][10][11][12][13][14][15][16]. From those studies, 6 psychosocial perceptions have emerged that influence the adoption of CTAs: trust in the government, beliefs about personal data, social norms, perceived personal and societal benefits, risk perceptions, and self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…The slowest time of finding secondary cases from the main case and unidentified contacts can also hamper the effectiveness of breaking the chain of transmission of COVID-19 (Keeling et al, 2020). Other obstacles, such as the risk of personal data leakage for users of health applications used for monitoring covid-19 tracing (Rahimi et al, 2021). Perceptions that arise for some people regarding the use of tracing applications in the UK such as confused in using them, assumptions and personal; little information about how the application functions; and Perception of a better tracing system, causing confusion to use this application (Williams et al, 2021 Based on the results of Bayesian analysis it was found that a total of 7770 contacts were identified, 1150 close contacts were symptomatic of the results.…”
Section: Contact Tracing Managementmentioning
confidence: 99%
“…so it is estimated that 36% of individuals with coronavirus infection show symptoms. Rahimi, Khoundabi et al / 2021 This study aims to analyze the factors that influence the use of mobile health applications for "contact tracing" and "symptom monitoring" of COVID-19.…”
Section: Contact Tracing Managementmentioning
confidence: 99%
“…Por ejemplo, Aydin et al (2015) encontró que los usuarios de atención médica utilizan cada vez más aplicaciones con este propósito. Rahimi et al, (2021) determinó que el género, la edad, el nivel de educación, la actitud frente a la tecnología y el miedo a contraer COVID-19 influyeron en la intención de usar este tipo de Apps. Con respecto a aplicaciones de actividad física, el uso es mayor en mujeres entre 25 y 50 años que residen en zonas donde la mayor parte de la población tiene un nivel socioeconómico bajo (Pontin et al, 2021).…”
Section: Introductionunclassified